Pre and Post Fusional Reserve Assessment following Orthoptic Exercise (Medical Forum Monthly, 2021)
Objective: Assess the Pre and Post Fusional Reserve Vergence (PFV) following Orthoptic Exercise.Study Design: A Longitudinal Interventional Based StudyPlace and Duration of Study: This study was conducted at the Isra Postgraduate Institute of Opthalmology and Muhammad Medical College from Oct. 2020 to April 2021.Materials and Methods: 60 patients that had CI were selected for this study. All of the patients were taught and prescribed the pencil push-up tests as the form of Orthoptic exercise which was to be carried out to improve CI. The Pre and Post PFV was measured and compared using the Chi-Square tests, the P-value was set at P-value ≤0.05.Results: Significant Different was seen in the Pre and Post Fusional Reserve Distance Positive (Pvalue≤0.01), Pre and Post Fusional Reserve Distance Negative (P-value=0.02), Pre and Post Fusional Reserve near Negative (P-value=0.01), and Pre and Post Fusional Reserve near Positive (P-value ≤0.01).Conclusion: Following Orthoptic Exercise Improvement was seen in the Post Fusional Reserve Vergence. Further studies can be to assess if Orthoptic Exercise can improve Near Point of Convergence or if it can improve symptoms of CI.